Real-Time Autonomous System of Navigation Using a Stereoscopic Camera - Mihalcea, Georgiana; Suciu, George; Vasilescu, Cristian (2018 International Conference on Communications (COMM), 2018)
Artificial intelligence is in a continuous development and automation of vehicles is a discussed subject. The navigation of any vehicle is based on obstacle avoidance, but it still challenges the field of automation because of the unpredictable environment. Usually, an algorithm for obstacle avoidance is based on several types of sensors. This article will present an evaluation of two algorithms, one using the mean estimation method and one using the threshold estimation method, both based on only one imaging sensor, which simplify the complexity of the system. The algorithms are based on 3D reconstruction of the environment and making the disparity map which is a matrix that contains the depth information of each pixel from an image. Both algorithms have been implemented in C++, using as device DUO MLX stereo camera on an embedded system with ARM processing unit (DUO VPC).